2020
DOI: 10.1505/146554820829403531
|View full text |Cite
|
Sign up to set email alerts
|

Underlying driving forces of forest cover changes due to the implementation of preservation policies in Iranian northern Zagros forests

Abstract: Many countries have implemented policies to reduce the negative effects of deforestation. In Iran, the Zagros Forest Preservation Plan (ZFPP) began in 2003. This study evaluates the effectiveness of ZFPP on land cover changes in two periods, before (1993–2002) and after (2002–2017) implementation of the plan. Logistic regression (LR) analysis was used to examine the effectiveness of key socio-economic, environmental and demographic drivers associated with deforestation activities. The results showed that desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Ignoring the participation of local residents in ecosystem restoration often results in conflicts between ecological restoration and residents' livelihoods so that ecosystem restoration cannot achieve the expected goals. For example, preservation in the Zagros Forest of Iran has not achieved the expected protection goals: after conservation in 2003, the deforestation rates were 0.4% and 0.5% from 1993 to 2002 and from 2003 to 2017, respectively (Heidarlou et al, 2020). The deforestation of forests closer to rivers, cities, and roads was more severe because the implementation of the conservation project could attract the participation of local people, and illegal logging by local residents for timber and grain was serious (Heidarlou et al, 2019).…”
Section: Perspectives In Achieving the Sdgs In Asia's Dryland Ecosyst...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ignoring the participation of local residents in ecosystem restoration often results in conflicts between ecological restoration and residents' livelihoods so that ecosystem restoration cannot achieve the expected goals. For example, preservation in the Zagros Forest of Iran has not achieved the expected protection goals: after conservation in 2003, the deforestation rates were 0.4% and 0.5% from 1993 to 2002 and from 2003 to 2017, respectively (Heidarlou et al, 2020). The deforestation of forests closer to rivers, cities, and roads was more severe because the implementation of the conservation project could attract the participation of local people, and illegal logging by local residents for timber and grain was serious (Heidarlou et al, 2019).…”
Section: Perspectives In Achieving the Sdgs In Asia's Dryland Ecosyst...mentioning
confidence: 99%
“…The Chinese Government implemented the Natural Forest Protection Programme (P13) in 1988 to ban or reduce natural forest logging (Bryan et al 2018;Delang & Wang, 2013;Liu et al, 2008). Iran implemented the Zagros Forest Preservation Plan (P17) in 2003 (Heidarlou et al, 2019), aiming to reduce forest destruction, protect habitats, improve the status of protected forests, and promote sustainable forest management (Heidarlou et al, 2020). Due to the differences in local participation and acceptance, the Zagros Natural Forest Preservation Plan in Iran is far from reaching the expected ecological goals.…”
Section: Natural Forest Restoration Programmesmentioning
confidence: 99%
“…Sardasht County, which is located in West Azarbaijan Province, northwest of Iran, was chosen as the study region, with a total area of around 138,000 ha ( Figure 1 ). The county holds 90% of the province’s forests and includes four major cities (Sardasht, Mirabad, Nalas, and Rabat) and 352 rural areas [ 17 ]. The 2016’s population census revealed that urban and rural areas had a population of 68,162 and 50,687, respectively, whose main activities are agriculture and animal husbandry.…”
Section: Methodsmentioning
confidence: 99%
“…In order to apply the forest management in this region, after the FNL, conservation projects were developed since 1997. Due to their shortcomings, conservation plans were not implemented and/or were implemented only in part [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These policies did not take into account the forest-dependent people (especially in the Zagros); as such, forests and grasslands were managed with both traditional and governmental participation. With an area of around 4,749,000 ha, the Zagros oak forests cover 20% of the vegetative area and 11 provinces of Iran, playing an important socioeconomic role (Roozitalab et al 2018, Beygi Heidarlou et al 2020b.…”
Section: Introductionmentioning
confidence: 99%